Intersections of ageing, gender, sexualities Multidisciplinary international perspectives - King, Andrew; Almack, Kathryn (Policy Press, 2019)
With an increasingly diverse ageing population, we need to understand how social divisions intersect to affect outcomes in later life. Gender and sexuality are recognised as key factors in determining a person's experience of later life but little research has been done into how age, gender and sexualities work together and with other divisions, including ethnicity and class, to form a range of inequalities and opportunities for people as they age. The collection brings together an international group of researchers and writers from Australia, Brazil, Denmark, Israel, Italy, Spain, South Africa, Sweden, Taiwan, the UK, and the USA, who argue for multiple, complex contextualised and spatialized approaches to understanding intersections of ageing, gender and sexualities and uneven outcomes in later life. The book highlights new ways of engaging with and thinking through questions related to ageing, gender and sexualities.